Integration of eddy current sensors into repair patches for fatigue reinforcement at rivet holes. (6th May 2021) - Schmid, Sebastian; Martens, Ulrike; Schomburg, Werner Karl; Schröder, Kai‐Uwe
Abstract: Fatigue cracks at rivet holes occur at advanced service life of aircrafts due to cyclic loading. As a repair method, adhesively bonded stiffener patches enhance the fatigue life of the structure by delaying crack initiation and reducing crack growth. Combining a crack sensor with a repair patch to a sensor‐based stiffener patch allows crack growth reduction and monitoring at the same time. This paper presents a feasibility study on the integration of eddy current sensors into carbon fibre reinforced plastic (CFRP) repair patches. To this end, a specific patch design is developed, and samples are manufactured by ultrasonic fabrication. The performance of the patches is investigated in fatigue tests in terms of 'crack reinforcement' and 'crack detection.' Both requirements are met. The undertaking of future efforts to tailor the sensor‐based repair patch concept to an individual application in aircraft maintenance seems reasonable.